The D614G Mutation in Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Spike Glycoprotein: A MiniReport - Arif Nur Muhammad Ansori (Indian Journal of Forensic Medicine & Toxicology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a quickly spreading virus that posesa major burden on global human health. Thus, it is essential to develop COVID-19 vaccines. Vaccinedevelopment might not be easy, as a consequence of mutations. This study aimed to demonstrate the D614Gmutation in SARS-CoV-2 spike glycoprotein from Indonesia. 102 isolates from the GISAID EpiCoVdatabase and the Wuhan-Hu-1 isolate (reference sequence) from GenBank, NCBI were used in this study.BioEdit employed to examine the D614G mutation in the spike glycoprotein of SARS-CoV-2. In this report,there are 56 D614G mutations among 102 SARS-CoV-2 isolates. In summary, this report might suggestthat the D614G mutation implicates the COVID-19 pandemic in Indonesia. Nevertheless, this report was apreliminary study and this study recommends expanding molecular epidemiology and surveillance programsto monitor COVID-19